Coral Reefs Health Status in the East Java: a Case Study in Banyuwangi, Situbondo, Probolinggo - Samuel, Pratama Diffi; Dewi, Citra Satrya Utama; Azmi, Nur Fadholi Ulul; Anam, M.Choirul; DP, Imas; Setyorini, Dewi Nur; Hariani, Dyah Fitri; Fatmawati, Riska (Research Journal of Life Science, 2021)
Coral reef ecosystems are among the most productive natural biodiversity resources  in tropical coastal areas, within seagrass beds and mangrove forests. Besides, coral reefs have very high ecological impacts and economic value that are managed well and sustainably. Also, healthy ecosystems will undoubtedly provide more incredible benefits and values, so studies need to be conducted to determine the health of coral reefs. While P2O LIPI is an institution that is the guardian of coral reef health data in Indonesia, there is limited information related to the coastal areas of East Java that has not been widely reported. This study aimed to find out the percentage of living hard corals and the health status of the ecosystem at three reef sites: Banyuwangi, Situbondo, and Probolinggo. Field surveys were carried out in June-July 2019, using the Line Intercept Transect (LIT) method. The materials used in this study are Self-Contain Underwater Breath Apparatus-SCUBA diving equipment, roll meters, and an underwater camera. The results showed that the hard coral cover living in Banyuwangi accounted for 28.91%, Situbondo was 31.20%, and Probolinggo (34.77%). Therefore, this study interpreted that the coral reef ecosystem was a moderate category (25% - 49.9%).